Instrumental and Sensory Analysis of the Properties of Traditional Chinese Fried Fritters - Daming Fan; Bowen Yan; Huizhang Lian; Jianxin Zhao; Hao Zhang (Journal of Chemistry)
The quality of traditional Chinese fried fritters is typically measured using human sensory evaluation techniques and physicochemical indices, the process of which is laborious and time-consuming. This study aimed to investigate the relationship between instrumental parameters, sensory criteria, and physicochemical indices. Significant correlations were found using principle component analysis. Volume, fat, texture, palatability, and instrumental parameters (hardness, fracturability, springiness, and gumminess) were found to be the main factors influencing the quality of Chinese fried fritters by principal component analysis (PCA) and instrumental methods, which were satisfactory replacement for human evaluation in correlation testing.